Video Company Profile AfterTaste - Jimmy Pratama; Cristiansen Cristiansen (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This community service program has the aim of increasing sales, reaching a wider sales market and adding insight to new consumers by using social media and the media is 59 second long and increase about 20 to 30 people on their instagram account. Partners in community service are Aftertaste CoffeShop, which is a shop engaged in the food and beverage sector, located at Komplek Kintamani Blok F no 7, Sungai Panas, Batam City. The method used in this activity is MDLC (multimedia development life cycle and implementation on social media. The implementation results show an increase in new marketing reach, an increase in turnover and an increase in new consumers.